Cybersecurity in Cloud-Based Industrial Control Systems - Holden Vance Everett; Maverick Sloan Archer (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
As industries increasingly integrate cloud-based Industrial Control Systems (ICS), the cyber threat landscape expands. While cloud computing offers scalability, cost efficiency, and remote accessibility, it also introduces security vulnerabilities that adversaries can exploit. This study explores AI-driven threat detection models, encryption techniques, and best practices to enhance ICS resilience. Key security measures, including intrusion detection systems, anomaly detection, and robust encryption mechanisms, are analyzed to mitigate cyber risks. The findings highlight the effectiveness of AI-based security solutions in identifying and preventing attacks, ensuring the reliability and integrity of ICS in cloud environments.